2017
DOI: 10.1103/physrevd.95.104050
|View full text |Cite
|
Sign up to set email alerts
|

Exotic rotational correlations in quantum geometry

Abstract: It is argued that the classical local inertial frame used to define rotational states of quantum systems is only approximate, and that geometry itself must also be rotationally quantized at the Planck scale. A Lorentz invariant statistical model of correlations in quantum geometry on larger scales predicts spacelike correlations that describe rotational fluctuations in the inertial frame. Fluctuations are estimated to significantly affect the gravity of quantum field states on a macroscopic scale, characterize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…Using standard algebraic methods [18,65,66], it can be shown that in an eigenstate ofτ 3 , τ 1 = τ 2 = 0 (38) and τ 2 1 = τ 2 2 = τ 2 −τ 2 3 /2 = t 2 P [l(l + 1) − m 2 ]/2. (39) Since m 2 ≤ l 2 , we can write a generalized uncertainty principle for quantum fluctuations in any three orthogonal directions:…”
Section: Nonlocal Information Projection and Uncertaintymentioning
confidence: 99%
“…Using standard algebraic methods [18,65,66], it can be shown that in an eigenstate ofτ 3 , τ 1 = τ 2 = 0 (38) and τ 2 1 = τ 2 2 = τ 2 −τ 2 3 /2 = t 2 P [l(l + 1) − m 2 ]/2. (39) Since m 2 ≤ l 2 , we can write a generalized uncertainty principle for quantum fluctuations in any three orthogonal directions:…”
Section: Nonlocal Information Projection and Uncertaintymentioning
confidence: 99%
“…Unlike the particle example, geometrical states are universal: they must entangle with all forms of matter and energy on a light cone in all directions, not just a single pair of particles. Their correlations describe the relationship of the local inertial frame of a world line to the rest of the universe [13][14][15].…”
Section: Physical Effects Of Exotic Correlationsmentioning
confidence: 99%
“…Various models mathematically suggest such nonclassicality [1,2,3,4,5], but it is not clear exactly how much the physical metric departs from the classical structure, nor how the effects of Planck-scale fluctuations affect the geodesic of an object on larger scales. Some estimates of the quantum deviations from a classical background [6,7,8,9,10,11,12,13,14], based on extrapolations of standard physics normalized to match black hole entropy, have suggested that quantum fluctuations could lead to positional decoherence on small but measurable scales (10 −18 m in a 1-m system). Moreover, these fluctuations of relative position are predicted to correlate spatially over distances small compared to the system size.…”
Section: Introductionmentioning
confidence: 99%